“Despicable, Disgusting, Repulsive!!!” Public Emotions and Moralities in Online Discussions About Violence Towards Refugees - Pantti, Mervi (Javnost-The Public, 2016)
This article analyses the affective-discursive work that the image of an anti-asylum seeker demonstrator dressed like a member of the Ku Klux Klan and waving a Finnish flag generated on online platforms in Finland. Specifically, the article focuses on how the vocabulary of disgust served to draw boundaries between “us” and “others”, thus reconstructing hierarchies of human worth and deservingness. The aim of the article is to discuss the role of disgust and related emotions in relation to what has become known as the European refugee crisis and whether the language of disgust allows for solidarity with the plight of asylum seekers.